Flight Dynamics and Abundance of Ips sexdentatus (Coleoptera: Curculionidae: Scolytinae) in Different Sawmills from Northern Spain: Differences between Local Pinus radiata (Pinales: Pinaceae) and Southern France Incoming P. pinaster Timber - Sergio López; Arturo Goldarazena (Psyche: A Journal of Entomology)
In January 2009, the windstorm “Klaus” struck the southern part of France, affecting 37.9 million m3 of maritime pine Pinus pinaster Aiton (Pinales: Pinaceae). This breeding plant material favored the outbreak of Ips sexdentatus (Börner) (Coleoptera: Curculionidae: Scolytinae). As much of this timber is imported to the Basque Country (northern Spain), a potential risk to conifer stands is generated, due to the emergence of the incoming beetles. Thus, flight dynamics and beetle abundance were compared in different sawmills, according to the timber species (either local P. radiata D. Don or imported P. pinaster). A maximum flight peak of I. sexdentatus was observed in mid-June in P. pinaster importing sawmills, whereas a second lighter peak occurred in September. In contrast, only a maximum peak in mid-June was observed in P. radiata inhabiting beetles, being significantly smaller than in local P. pinaster trading sawmills. In addition, significant differences were found between imported P. pinaster and P. radiata regarding the number of insects beneath the bark. The development of IPM strategies for controlling I. sexdentatus populations is recommended, due to the insect abundance found in P. pinaster imported timber.